Breakthrough SARS‐CoV‐2 infections among BBV‐152 (COVAXIN®) and AZD1222 (COVISHIELDTM) recipients: Report from the eastern state of India. Issue 3 (13th October 2021) - Dash, Girish C.; Subhadra, Subhra; Turuk, Jyotirmayee; Parai, Debaprasad; Rath, Sonalika; Sabat, Jyotsnamayee; Rout, Usha K.; Kanungo, Srikanta; Choudhary, Hari R.; Nanda, Rashmi R.; Pattnaik, Matrujyoti; Pati, Sanghamitra; et al.
Abstract: In this study, we attempted to record the breakthrough cases reported through passive and voluntary reporting at various healthcare facilities from different districts of Odisha, their clinical presentation, requirement of hospitalization postinfection, and antibody titer against spike antigen. Nasopharyngeal swab and serum samples alongwith demographic, clinical presentation and requirement of hospitalization postinfection were collected from vaccinated individuals through passive and voluntary reporting to various healthcare facilities of Odisha state to detect the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) virus infection and quantitative estimation of antibody titers. A total of 274 samples were found to be positive after 14 days of receiving complete doses of the vaccines. More than 83.2% of the individuals were found to be symptomatic with 9.9% of those required hospitalization. The seropositivity in individuals receiving Covishield (96.7%) was significantly higher than in Covaxin (77.1%). Hospitalized patients were having less median antibody titers than individuals in home isolation. The median age for breakthrough infection among the referred cases was 47.0 years (interquartile range [IQR]: 28.0) with a significantly older age group among Covishield recipients. The median spike receptor binding domain IgG titer values for Covaxin and Covishield recipients were 213.5 AU/ml (IQR: 537.5) and 647.5 AU/ml (IQR: 1645.1), respectively. The results reported here highlight the need for systematic data capture for the breakthrough infections to monitor the emergence of any vaccine escape variants and to plan the next steps in the coronavirus disease‐19 (COVID‐19) vaccine development by understanding the link between clinical protection and measured immunity against SARS‐CoV‐2 infection.